Creative Carbon Accounting—A Reply to "The Wood, the Trees, or the Forest? Carbon in Trees in Tasmanian State Forest: A Response to Comments". (17th May 2012) - Dean, Christopher
Abstract : Moroni et al. (2012) made forty claims which misrepresent my earlier reply to their work (Dean, 2011) and if left unrefuted, might mislead all but the most expert reader—I cover seven of the most important ones here. Firstly, in my earlier paper I had calculated a conservative carbon deficit in State forests due to logging of the most-targeted forest types—mature wet-eucalypt—by clearfell, burn and sow to yield even-aged eucalypt regeneration. That deficit was conservative as a range of stand ages were used even though most carbon flux through logging has been from the old-growth subset. It was additionally conservative at the landscape-scale as inclusion of conversion to plantation and logging of other primary-forest types would have yielded a larger carbon deficit, not a smaller one, as implied in Moroni et al. (2012). Secondly, their claim that I applied "carbon saturation" at the landscape-scale is incorrect. Instead I applied carbon carrying capacity at that scale and included different stands ages in its calculation (by definition). Conversely, Moroni et al. (2012) produce the "confusion" which they claim to observe by advocating the use of "carbon saturation" at the landscape-scale, which can have no practical usage.